Proliferation and migration of oral squamous cell carcinoma via ferritin heavy chain. A systematic review. - Shunmugavelu, Dr. Karthik; M.D.S, Dr. N . Parthiban (Student’s Journal of Health Research Africa, 2026)
Background Dysregulated iron metabolism is increasingly recognized as a driver of tumor progression in head and neck malignancies. Ferritin heavy chain (FTH1), a central regulator of intracellular iron storage and redox balance, has been implicated in ferroptosis resistance, proliferation and metastatic behaviour. Its mechanistic relevance in oral squamous cell carcinoma (OSCC) requires structured synthesis. Objective To systematically evaluate evidence regarding the role of FTH1 in promoting proliferation, migration and therapeutic resistance in OSCC and related head and neck squamous cell carcinoma (HNSCC). Methods A systematic review was conducted according to PRISMA guidelines. Electronic databases including PubMed, Scopus, Embase, Web of Science and LILACS were searched for studies published between 2020 and 2024 using combinations of the terms “ferritin,” “FTH1,” “oral cancer,” “OSCC,” “HNSCC,” and “ferroptosis.” Eligible studies included original research evaluating FTH1 expression, functional assays, mechanistic pathways, or clinical correlations in OSCC/HNSCC. Reviews, editorials and unrelated iron metabolism studies were excluded. Data extracted included study design, sample type, FTH1 expression patterns, molecular pathways, effects on proliferation, migration, EMT, ferroptosis and prognostic associations. Results Five eligible studies demonstrated consistent overexpression of FTH1 in OSCC/HNSCC tissues compared with controls. Functional analyses revealed that FTH1 promotes tumor cell proliferation and invasion by maintaining iron homeostasis, suppressing lipid peroxidation and inhibiting ferroptosis. Knockdown experiments increased reactive oxygen species accumulation and reduced migratory capacity. Clinically, elevated FTH1 expression correlated with lymph node metastasis, poor prognosis and resistance to chemotherapy and radiotherapy. Future Directions Larger OSCC-specific cohorts and mechanistic studies focusing on ferroptosis modulation, tumor microenvironment interactions and therapeutic targeting of FTH1 are required to validate its biomarker and translational potential.